Metabolism of inflammation limited by AMPK and pseudo-starvation. - O'NEILL, LUKE (My University, 2013)
Metabolic changes in cells that participate in inflammation, such as activated macrophages and T-helper 17 cells, include a shift towards enhanced glucose uptake, glycolysis and increased activity of the pentose phosphate pathway. Opposing roles in these changes for hypoxia-inducible factor 1α and AMP-activated protein kinase have been proposed. By contrast, anti-inflammatory cells, such as M2 macrophages, regulatory T cells and quiescent memory T cells, have lower glycolytic rates and higher levels of oxidative metabolism. Some anti-inflammatory agents might act by inducing, through activation of AMP-activated protein kinase, a state akin to pseudo-starvation. Altered metabolism may thus participate in the signal-directed programs that promote or inhibit inflammation.
PUBLISHED
Keywords: inflammation; Immunology, Inflammation & Infection